EFFICACY AND SAFETY OF LIPID-LOWERING DRUGS IN PRIMARY AND SECONDARY PREVENTION OF CARDIOVASCULAR DISEASES IN THE ELDERLY - E. A. Ushkalova; O. N. Tkacheva; N. K. Runikhina; N. A. Chukhareva; A. Yu. Bevz (Столичная издательская компания, 2016)
Effect of hyperlipidemia on morbidity and mortality in elderly patients is considered. Authors also cover issues of efficacy and safety of lipid-lowering therapy in primary and secondary prevention of cardiovascular diseases in patients ≥80 years of age who are the most quickly growing group of population and have the highest cardiovascular risk. They stress the need to take into account polymorbidity and polypharmacy that increase the risk of adverse reactions due to the use of both statins and their drug-drug interactions, which requires an assessment of risk/benefit ratio. In addition, there is a need for development of reliable prognostic tools to predict relevant outcomes (e.g., stroke, decrease in functionality/independence, quality of life reduction) and rationales for lipid-lowering therapy in the elderly and also their adherence to treatment.